Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru (Studi Kasus di SMK Sultan Alyasini) - Warda, Uliyatul; Abidin, Moch. Zainal; Wahidmurni, Wahidmurni (Universitas Yudharta Pasuruan, 2025)
The aim of this research is to reveal (1) the concept of increasing supervision of the Principal of Sultan Alyasini Vocational School in increasing teacher professionalism, and (2) the implementation of Principal supervision in increasing teacher professionalism. To achieve the research objectives, a qualitative approach was applied with a case study type of research. Data was collected through interviews, observation and document study, with data sources including; Principal, vice-waka and teachers. Data analysis by means of data condensation, data presentation, and drawing conclusions. The technique for checking the validity of the data uses triangulation. Data collection techniques and data sources. The results of the research show that (1) the concept of increasing the supervision of the Principal in increasing teacher professionalism is designed by having teacher discipline, maximizing rewards and punishments, and holding teacher and employee report cards every month, (2) the implementation of Principal supervision in increasing teacher professionalism is carried out by providing rules for teachers, giving rewards with minimum working hours, apart from that there is also punishment by giving SP 1, SP 2, SP 3, apart from that the principal Sultan Alyasini also holds report cards for every teacher and employee every month which is assisted by the deputy principals.